Multiple plates subducting beneath Colombia, as illuminated by seismicity and velocity from the joint inversion of seismic and gravity data (2016)
Subduction beneath the northernmost Andes in Colombia is complex. Based on seismicity distributions, multiple segments of slab appear to be subducting, and arc volcanism ceases north of 5° N. Here, we illuminate the subduction system through hypocentral relocations and Vp and Vs models resulting from the joint inversion of local body wave arrivals, surface wave dispersion measurements, and gravity data. The simultaneous use of multiple data types takes advantage of the differing sensitivities of each data type, resulting in velocity models that have improved resolution at both shallower and deeper depths than would result from traditional travel time tomography alone. The relocated earthquake dataset and velocity model clearly indicate a tear in the Nazca slab at 5° N, corresponding to a 250-km shift in slab seismicity and the termination of arc volcanism. North of this tear, the slab is flat, and it comprises slabs of two sources: the Nazca and Caribbean plates. The Bucaramanga nest, a small region of among the most intense intermediate-depth seismicity globally, is associated with the boundary between these two plates and possibly with a zone of melting or elevated water content, based on reduced Vp and increased Vp/Vs. We also use relocated seismicity to identify two new faults in the South American plate, one related to plate convergence and one highlighted by induced seismicity.